2011
DOI: 10.1080/17470218.2011.570353
|View full text |Cite
|
Sign up to set email alerts
|

When Less is Heard than Meets the Ear: Change Deafness in a Telephone Conversation

Abstract: During a conversation, we hear the sound of the talker as well as the intended message. Traditional models of speech perception posit that acoustic details of a talker's voice are not encoded with the message whereas more recent models propose that talker identity is automatically encoded. When shadowing speech, listeners often fail to detect a change in talker identity. The present study was designed to investigate whether talker changes would be detected when listeners are actively engaged in a normal conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 57 publications
4
44
1
1
Order By: Relevance
“…Indeed, evidence from behavioral studies suggests that participants often failed to notice changes in a visual (Levin, Simons, Angelone, & Chabris, 2002;Sinnett, Costa, & Soto-Faraco, 2006;Triesch. Ballard, Hayhoe, & Sullivan, 2003) or auditory scene (Fenn et al, 2011;Sinnett et al, 2006;Vitevitch, 2003) when the change was unexpected-even when the objects were to be attended (Caplovitz, Fendrich. & Hughes, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, evidence from behavioral studies suggests that participants often failed to notice changes in a visual (Levin, Simons, Angelone, & Chabris, 2002;Sinnett, Costa, & Soto-Faraco, 2006;Triesch. Ballard, Hayhoe, & Sullivan, 2003) or auditory scene (Fenn et al, 2011;Sinnett et al, 2006;Vitevitch, 2003) when the change was unexpected-even when the objects were to be attended (Caplovitz, Fendrich. & Hughes, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…P to A, A to I and P to I) when follow-up post-surgical data is available for these patients. However even with these investigations of predictions over time, these studies cannot test whether the relationships are truly causal and this will require experimental studies such as those conducted by Fisher & Johnston (1996) [45]. In this study we only explored I, A and P and not the contextual factors.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, previous studies on visual change detection have demonstrated that even pronounced changes within a complex visual scene can remain unnoticed if they occur after a short interruption of the visual presentation (Simons & Rensink, 2005;Rensink, 2002). Recently, several psychophysical experiments provided evidence for the existence of a similar effect in the auditory modality (Backer & Alain, 2012;Fenn et al, 2011;Vitevitch & Donoso, 2011;Gregg & Samuel, 2008Eramudugolla, McAnally, Martin, Irvine, & Mattingley, 2008;Pavani & Turatto, 2008;Eramudugolla, Irvine, McAnally, Martin, & Mattingley, 2005;Vitevitch, 2003). In a similar manner to visual change blindness, this change deafness emerges when listeners have to monitor demanding auditory scenes consisting of several streams (Gregg & Samuel, 2008Eramudugolla et al, 2005Eramudugolla et al, , 2008Pavani & Turatto, 2008) or when concentrating on a specific aspect of the auditory input (Fenn et al, 2011;Vitevitch, 2003).…”
Section: Introductionmentioning
confidence: 94%